PHOTOTHERAPY: CUTANEOUS AND SYSTEMIC REJUVENATION - Bohdana Doskaliuk (Anti-Aging Eastern Europe, 2025)
The convergence of biomedical innovation and lifestyle medicine has propelled phototherapy to the forefront of anti-ageing interventions. As interest grows in non-invasive strategies to enhance cellular resilience and systemic health, photobiomodulation, particularly through red and blue light therapies, has demonstrated promising applications in dermatology, ophthalmology, neurology, and cardiovascular care. This article synthesises current evidence on Low-Level Laser Therapy (LLLT) and Light Emitting Diode (LED) therapy, examining their mechanistic foundations, clinical efficacy, and therapeutic precision. Red light has been shown to improve mitochondrial function, collagen production, and vascular dynamics, while blue light offers notable antimicrobial and immunomodulatory effects. The therapeutic impact depends on wavelength, energy dose, and exposure parameters, highlighting the necessity for personalised protocols. Despite challenges in standardisation, phototherapy holds considerable potential as an adjunctive tool in holistic, technology-driven anti-ageing medicine.